2014
DOI: 10.1111/iej.12221
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance of pulp health 17 years after root fracture in a maxillary incisor illustrating the diagnostic benefits of cone bean computed tomography

Abstract: The dental pulp is characterized by the ability to heal spontaneously in cases of root fracture. CBCT has advantages in diagnosing root fractures over intra-oral radiographs. CBCT should be employed with caution due to its increased radiation dose compared with periapical radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Kullman and Al Sane in a systematic review in 2012 reported a lack of evidence‐based research on radiographic methods although there was support for the current recommendations in the IADT guidelines. A PubMed search using the same search words for articles published since 2012 revealed no papers with specific recommendations on guidelines, while a number of articles advocated judicious use of CBCT when considered clinically appropriate . From a research and clinical perspective, the advantages of standardized documentation utilizing CBCT were recently demonstrated in a case series of avulsed teeth where replantation was delayed and where ankylosis‐related resorption eventuated.…”
Section: Radiographic Techniquementioning
confidence: 99%
“…Kullman and Al Sane in a systematic review in 2012 reported a lack of evidence‐based research on radiographic methods although there was support for the current recommendations in the IADT guidelines. A PubMed search using the same search words for articles published since 2012 revealed no papers with specific recommendations on guidelines, while a number of articles advocated judicious use of CBCT when considered clinically appropriate . From a research and clinical perspective, the advantages of standardized documentation utilizing CBCT were recently demonstrated in a case series of avulsed teeth where replantation was delayed and where ankylosis‐related resorption eventuated.…”
Section: Radiographic Techniquementioning
confidence: 99%
“…Due to superimposition of anatomical and restorative entities, projection radiography has a low sensitivity for detection of fractures. CBCT was considered the most reliable imaging modality to resolve these difficulties [18,19,26]. In our case, sagittal CBCT slices show the location of fractures and dislocation of the coronal fragment in tooth 11.…”
Section: Discussionmentioning
confidence: 83%
“…Only in one of the 42 analyzed cases, after 36 months from the therapy, tooth extraction was required because of diastasis, mobility and phlogosis. The healing of the horizontal root fractures without treatment is presented in many reports with a rate superior to 80% [ 7 , 15 ]. Makowiecki et al ., reported a case, found incidentally on a routine radiographic examination, maintaining the pulpal health up to 17 years after root fracture [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal root fractures in the apical and middle third are not always symptomatic, and can be incidentally identified during routine examinations. In these cases, treatment is often non required and spontaneous healing is frequently reported [ 13 - 15 ]. In the other cases, the patient can report pain during chewing.…”
Section: Introductionmentioning
confidence: 99%